Hubungan Pelayanan Rawat Jalan Pasien Dengan Premi Badan Penyelenggara Jaminan Sosial (Bpjs) Berdasarkan Uu No 24 Tahun 2011 - Zahra Luthfiyah, Fasya (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
In this study, the role of BPJS as a provider of health insurance as a form of public service in Indonesia will be explored. This research is normative and uses a comparative approach. The results of the study show that all types of services, both goods and services, which in principle are the responsibility of government agencies or are the duties and functions of government agencies at the central, regional, and state or regional government-owned enterprises, can be defined as various forms of service. In an effort to ensure that all Indonesian people have access to adequate basic needs, the Social Security Administration Agency (BPJS) is one of the bodies responsible for administering social security programs. BPJS adheres to the principles of human rights, benefits, and social justice to ensure that all Indonesian citizens can meet their basic needs for a decent life. The results of this study BPJS Kesehatan is a national health insurance program in Indonesia which aims to provide equal access to health services to all Indonesian citizens. BPJS Kesehatan covers outpatient, inpatient and other health facilities. Legal protection related to the rights of patients who use BPJS for health, in obtaining health services the government has stipulated RI Law Number 24 of 2011 which stipulates two BUMNs, namely PT Askes (Persero) and PT Jamsostek (Persero) which were changed to form Service Agencies. The public to carry out the five programs mandated by Law Number 40 of 2004, namely the Health Insurance program for BPJS Health and other programs is handed over to BPJS Employment. BPJS Health sometimes faces challenges and complaints from patients related to the services provided.